An Approach–Avoidance Framework of Workplace Aggression - Ferris, D. Lance; Yan, Ming; Lim, Vivien K. G.; Chen, Yuanyi; Fatimah, Shereen (Academy of Management Journal, 2016)
The number of constructs developed to assess workplace aggression has flourished in recent years, leading to confusion over what meaningful differences exist (if any) between the constructs. We arg...